2009
DOI: 10.1093/nar/gkp674
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of two new transcriptional variants of the human p63 gene

Abstract: p63 belongs to a family of transcription factors, which, while demonstrating striking conservation of functional domains, regulate distinct biological functions. Its principal role is in the regulation of epithelial commitment, differentiation and maintenance programs, during embryogenesis and in adult tissues. The p63 gene has a complex transcriptional pattern, producing two subclasses of N-terminal isoforms (TA and ΔN) which are alternatively spliced at the C-terminus. Here, we report the identification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
120
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 30 publications
(39 reference statements)
0
120
0
2
Order By: Relevance
“…Consistent with earlier reports, we demonstrated that DNp63a is the predominant isoform in both HaCaT and A431 cell lines. 15,16 A faint band corresponding to TAp63g was detected upon immunoblot analysis using a TA-specific antibody (Supplementary Figure S1). To determine the effect of DNp63a on PTEN, we knocked down p63 in both mutant p53 (A431 and HaCaT, Figure 1a) and wild-type p53 (primary human keratinocytes, Figure 1b) backgrounds.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with earlier reports, we demonstrated that DNp63a is the predominant isoform in both HaCaT and A431 cell lines. 15,16 A faint band corresponding to TAp63g was detected upon immunoblot analysis using a TA-specific antibody (Supplementary Figure S1). To determine the effect of DNp63a on PTEN, we knocked down p63 in both mutant p53 (A431 and HaCaT, Figure 1a) and wild-type p53 (primary human keratinocytes, Figure 1b) backgrounds.…”
Section: Resultsmentioning
confidence: 99%
“…In silico analysis predicted the d isoform (skipping exon [12][13] and the e isoform (premature termination in intron 10 retaining the 5 0 -portion of intron 10 with a stop codon p63 is the most recently discovered but the most ancient member of the p53 family [8][9][10][11][12][13][14][15]28 ( Figure 1). As indicated above, p63 is transcribed from two promoters, giving rise to proteins that may (TAp63 isoforms) or may not (DNp63 isoforms) contain the TA, 1 and alternative splicing at the 3 0 -end produces additional proteins (a-e isoforms), 29 although there is no in vivo evidence for two latter isoforms. Whereas the TAp63 proteins are capable of transactivation, the DNp63 forms can also act in a dominant-negative fashion to counteract the transcriptional activity of the TAp63 isoforms and p53.…”
Section: Open Questionsmentioning
confidence: 99%
“…1 By encoding two different N-termini (TA and DN) and multiple C-termini by alternative splicing, the TP63 gene generates multiple-protein isoforms. 2,3 All p63 isoforms contain identical DNA binding and oligomerization domains and are able to transactivate p53-responsive and specific target genes. 4 Moreover, p53 gene members functions sometimes in an interdependent way.…”
Section: Do Human Skps Age Like In Mice and Depend Onmentioning
confidence: 99%